Bentuk dan Peran Kapital Sosial dalam Percepatan Penurunan Stunting di Desa Pandawangi, Lombok Timur - Husnul Maad; Triyanti Anugrahini (Prodi Sosiologi Universitas Mataram, 2021)
The Poor nutritional status of children under five years of age remains a major concern in Indonesia. Based on RISKESDAS (Basic Health Survey) 2018, NTB province was listed as one of the 10 provinces with the highest stunting rates in Indonesia with 33,49 children are stunted, and Lombok Timur district was the highest stunting in NTB with prevalence reached 43, 5 %. Considering the long-lasting effects of child malnutrition, the district government of Lombok Timur put stunting reduction program as a priority. In 2017, Pandanwangi village was selected as one pilot village for implementing the national strategy to accelerate stunting prevention and reduction. Pandanwangi village successfully implemented integrated approach dealing with stunting reduction through specific and sensitive nutrition intervention. The aim of the study was to identify the form and role of social capital on stunting reduction program activities in Pandanwangi village. This was a qualitative study on collecting information from informants the health and non-health sector. Data were collected through in-depth interviews, observation and focus group discussion. The results showed that several forms of social capital included in social bonding, bridging, linking and played a role in the acceleration of the decline in stunting. Based on the research results, each type of social capital plays an important role in creating a enabling environment in stunting reduction efforts. The results of the study also showed a synergy between various forms of social capital that allowed the community to accelerate stunting reduction in Pandawangi Village.